The induction of autoimmune hepatitis in the human leucocyte antigen‐DR4 non‐obese diabetic mice autoimmune hepatitis mouse model. (23rd August 2016) - Yuksel, M.; Xiao, X.; Tai, N.; Vijay, G. M.; Gülden, E.; Beland, K.; Lapierre, P.; Alvarez, F.; Hu, Z.; Colle, I.; Ma, Y.; Wen, L.
Summary: Autoimmune hepatitis (AIH) is a chronic liver disease characterized by progressive inflammation, female preponderance and seropositivity for autoantibodies such as anti‐smooth muscle actin and/or anti‐nuclear, anti‐liver kidney microsomal type 1 (anti‐LKM1) and anti‐liver cytosol type 1 (anti‐LC1) in more than 80% of cases. AIH is linked strongly to several major histocompatibility complex (MHC) alleles, including human leucocyte antigen (HLA)‐DR3, ‐DR7 and ‐DR13. HLA‐DR4 has the second strongest association with adult AIH, after HLA‐DR3. We investigated the role of HLA‐DR4 in the development of AIH by immunization of HLA‐DR4 (DR4) transgenic non‐obese diabetic (NOD) mice with DNA coding for human CYP2D6/FTCD fusion autoantigen. Immunization of DR4 mice leads to sustained mild liver injury, as assessed biochemically by elevated alanine aminotransferase, histologically by interface hepatitis, plasma cell infiltration and mild fibrosis and immunologically by the development of anti‐LKM1/anti‐LC1 antibodies. In addition, livers from DR4 mice had fewer regulatory T cells (Tregs ), which had decreased programmed death (PD)‐1 expression. Splenic Tregs from these mice also showed impaired inhibitory capacity. Furthermore, DR4 expression enhanced the activation status of CD8 + T cells, macrophages and dendritic cells in naive DR4 mice compared to naive wild‐type (WT) NOD mice. Our results demonstrate that HLA‐DR4 is a susceptibility factor for the development of AIH. Impaired suppressive function of Tregs and reduced PD‐1 expression may result in spontaneous activation of key immune cell subsets, such as antigen‐presenting cells and CD8 + T effectors, facilitating the induction of AIH and persistent liver damage. Abstract : Using HLA‐DR4 transgenic mouse model, we have demonstrated that HLA‐DR4 is a susceptibility factor for the development of autoimmune hepatitis upon immunization with autoantigen.